Keharmonisan keluarga pada wanita yang tinggal di rumah mertua: Bagaimana peran kematangan emosi dan penyesuaian diri? - Trian Asminatun; IGAA Noviekayati; Aliffia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract This research aims to determine the relationship between emotional maturity and self-adjustment with family harmony in married women who live with their mother-in-law. The method used in this research is a quantitative method with multiple linear regression analysis techniques. Sample determination was done using the Probability Sampling Technique with the assistance of G Power calculations, with a total of 155 married women who live with their mother-in-law. Data analysis was conducted using the Statistical Package for Social Science For Windows (SPSS) version 25. Based on the results of the data analysis, it can be observed that there is a positive relationship between emotional maturity and self-adjustment with family harmony in married women who live with their mother-in-law. This proves that the hypothesis proposed by the researcher is accepted. Keywords: Emotional maturity, self-adjustment, family harmony.